Predictors of Poststroke Driving or Riding in Indian Stroke Patients (POINT Study). Issue 4 (June 2013) - Bose, Shiti; Kaur, Paramdeep; Dhillon, Sudeepa; Raju, Rinu Susan; Pandian, Jeyaraj D.
Background: There is no information regarding the proportion of stroke patients who drive or ride after a stroke from developing countries. Aim: We aimed to study the predictors of poststroke driving or riding and its impact on social life in Indian patients. Methods This study was done in the stroke and neurology clinics of Christian Medical College, Ludhiana, from May 1, 2008 to May 31, 2010. Patients were recruited if they had completed ≥1-year follow-up. Subjects were interviewed using a structured questionnaire. Stroke outcome was assessed by using the modified Rankin scale. Outcome was classified as good (modified Rankin scale ≤2) and poor (modified Rankin scale >2). Results: Two hundred and one patients were interviewed. Mean age was 58·0 ± 13·4 years (median 59 years, range 17–85 years), 139 (69·2%) were men. The mean duration of follow-up was 37·4 ± 29·2 months (range 19–210 months). Out of 201 patients, 132 (65·7%) drove or rode before stroke and among them only 54 (40·9%) returned to driving or riding after stroke [men 53 (98·1%)]. Among the 78 who did not return to driving or riding, 51 (65·4%) had an impact on social life. In the multivariate logistic regression analysis, the predictors of inability to drive were lower education (odds ratio 0·32, confidence interval 0·12–0·89, P = 0·03), unemployment (odds ratio 4·59, confidence interval 1·67–12·6, P = 0·003), and poor outcome (odds ratio 3·97, confidence interval 1·06–14·8, P = 0·04). Conclusions: Only 40·9% of the patients returned to driving or riding. Lower education, unemployment, and poor recovery were the predictors of inability to drive or ride. Inability to drive had a major impact in their social life.